Employee Performance Termination - Fernandes Ginting, Ginta; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2024)
This research was conducted to examine the influence of leadership style on employee performance with organizational strategy as an intervening variable. By using quantitative research, primary data sources and collecting data by conducting questionnaires and sharing them with respondents, the population of this study was 80 employees and the sample used was also 80 respondents using a saturated sampling technique as the sampling technique. This research model uses phat analysis. The results of this research are as follows: Leadership style has a positive and insignificant effect with a value of 0.053 and a significant value of 0.172 > 0.05. BPJS Employment Sumbagut Regional Office. Leadership style has a positive and significant effect on Organizational Strategy with a value of 0.785 and a significant value of 0.000 <0.05. BPJS Employment Sumbagut Regional Office. Organizational Strategy has a positive and significant effect on Employee Performance with a value of 0.898 and a significant value of 0.000 <0.05 at. BPJS Employment Sumbagut Regional Office. Leadership Style has an indirect effect on Employee Performance positively and significantly through Organizational Strategy with a value of 0.705 and a significant value of 0.000 <0.05 at. BPJS Employment Sumbagut Regional Office.